Characterizing the patient experience of physical restraint in psychiatric settings via a linguistic, sentiment, and metaphor analysis - Cristiano Nichini; Chiara Barattieri di San Pietro; Biagio Scalingi; Eleonora Alecci; Luca Toschi; Simone Cavallotti; Anna Chiara Cigognini; Federico Durbano; Silvia Ferraris; Patrizia Santinon; Chiara Pompei; Federico Frau; et al. (Scientific Reports)
Abstract Physical Restraint (PR) is a coercive procedure used in emergency psychiatric care to ensure safety in life-threatening situations. Because of its traumatic nature, studies emphasize the importance of considering the patient’s subjective experience. We pursued this aim by overcoming classic qualitative approaches and innovatively applying a multilayered semiautomated language analysis to a corpus of narratives about PR collected from 99 individuals across seven mental health services in Italy. Compared to a reference corpus, PR narratives were characterized by reduced fluency and lexical density, yet a greater use of emotional and cognitive terms, verbs, and first-person singular pronouns. Sadness was the most represented emotion, followed by anger and fear. One-third of the PR narratives contained at least one metaphor, with Animals and War/Prison as the most distinctive source domains. The quality and length of the PR experience impacted both the structure and the sentiment of the narratives. Findings confirm the distressful nature of PR but also point to the use of various linguistic mechanisms which might serve as an early adaptive response toward healing from the traumatic experience. Overall, the study highlights the importance of Natural Language Processing as an unobtrusive window into subjective experience, offering insights for therapeutic choices.